Application of graphene‐based nanostructures in dye‐sensitized solar cells. Issue 12 (4th October 2013) - Kavan, Ladislav; Yum, Jun‐Ho; Graetzel, Michael
<x xml:space="preserve">Abstract</x> The paper reviews recent advances in the application of graphene and related materials, viz. graphene nanoplatelets (GNP), functionalized graphene sheets (FGS), graphene oxide (GO), and reduced graphene oxide (rGO) as electrode building materials in dye‐sensitized solar cell (DSC). Graphene promises multifaceted use in DSC: as prospective sensitizer, photoanode additive, current collector, and electrocatalyst for the redox‐shuttle turnover. Of particular significance is the use of graphene as cathode catalyst in the state of art Co‐mediated solar cells. Here, it can successfully replace platinum without any compromise on the electrode's catalytic activity, associated with good optical transparency.